SIGNIFICANCE OF SUBSTRATE TEMPERATURE ON ELECTRICAL CONDUCTIVITY, HALL EFFECT, AND THICKNESS OF BILAYER HETEROJUCTION ORGANIC SOLAR CELL USING RHODOMYRTUS TOMENTOSA (AITON) HASSK AND IXORA COCCINEA L DYE (Jurnal Teknologi (Sciences & Engineering), 2016)
In this work, Indium Tin oxide (ITO) glass used was 27ËšC to 200ËšC as substrate. The polymer used was Poly (3-Dodecylthiophene) (P3DT) thin film, Ixora coccinea L dan Rhodomyrtus tomentosa (Aiton) Hassk. as natural dye. The P3DT films were prepared using electrochemistry method at room temperature. Then, the natural dye was prepared layer by layer via spin coating method. Influence of heat treatment on the electrical properties and the efficiency of the system were investigated by Four Point Probes (FPP) under different light radiation (range of 0 Wm-2 to 200Wm-2), Hall Effect and thicknesss measurement. The electrical conductivity of the solar cell system increased with the increment of light radiations and the temperature of substrates. From Hall Effect measurement, the type of sample, Hall mobility, and highest charge carrier in the sample obtained. The thin film thickness was determined. The results show that the sample is suitable for further solar cell fabrications.